2022
DOI: 10.7202/1086427ar
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Indigenous Content Into K-12 Curriculum: Supports for Teachers in Provincial and Territorial Policy and Post-Secondary Education Spaces

Abstract: In an era of learning truth and working towards reconciliation with Indigenous peoples, education institutions across Canada are in the midst of decolonizing their education spaces. Fundamental to this process are the Truth and Reconciliation Commission Calls to Action to educate settler teacher candidates to develop culturally appropriate curricula and incorporate Indigenous content into their teaching practices. Little research has reviewed institutional responses to these recommendations. To fill this gap, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Although it is still common to see classrooms omit discussions of Indigenous content, the implementation of such content should happen in every course to meet the demands of both Reconciliation as well as the outcomes listed in Indigenous-focused ministry documents. Webb, 2022). One can attribute this to the ways in which teacher candidates learn within the province, as both the University of Saskatchewan and the University of Regina incorporate "Indigenous knowledge and treaty education" in their education programs (Martin, 2017, para.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is still common to see classrooms omit discussions of Indigenous content, the implementation of such content should happen in every course to meet the demands of both Reconciliation as well as the outcomes listed in Indigenous-focused ministry documents. Webb, 2022). One can attribute this to the ways in which teacher candidates learn within the province, as both the University of Saskatchewan and the University of Regina incorporate "Indigenous knowledge and treaty education" in their education programs (Martin, 2017, para.…”
mentioning
confidence: 99%
“…Still, there is evidence for the necessity of further inclusion. For example, research conducted by the Canadian Teachers' Federation showed that only 20% of teachers believed their current knowledge of Indigenous content was substantial enough to lead to proper teaching of the material (Mashford-Pringle & Webb, 2022). This becomes more pertinent when considered systemically, as teachers' lack of knowledge has been found to lead to higher drop-out rates for Indigenous students as well as to the denial of racism by teachers in educational settings (ACLRC, 2021;Bonam et al, 2018).…”
mentioning
confidence: 99%